HUBUNGAN PAPARAN DEBU PM2.5TERHADAP GANGGUAN FUNGSI PARU PADA PENGEMUDI BUS RAPID TRANSIT(BRT) SEMARANG - Rifa Attin Nur; Ari Suwondo; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
PM2.5 is produced by one of them by gas emissions from moving sources such as vehicles. PM2.5 in the air will be inhaled in, deposited in the lungs to the alveoli and can subsequently result in a decrease in lung function leading to pulmonary function disorders. The pulmonary function disorder can be measurements by vital lung capacity using spirometry. Jobs with a high risk of being exposed to air pollutants, especially PM2.5 are related to traffic, one of which is the bus driver. Semarang BRT drivers feel symptoms of pulmonary dysfunction such as coughing and sneezing when working is reinforced by observation in a dusty terminal area. Individual characteristics that affect vital lung capacity are age, work period, nutritional status, history of pulmonary disease, smoking habits, and exercise habits. The purpose of this study was to determine and analyze the relationship of exposure to PM2.5 dust with pulmonary function disorders in Semarang BRT drivers. The type of this research is observational analytic with a cross-sectional approach and quantitative analysis method. The population in this study was 33 drivers from corridors II, III and IV with a total sampling method. Bivariate analysis was carried out by the Chi-Square test (α = 0.05). The results showed that all variables were age (sig = 0.368), work period (sig = 0.707), nutritional status (sig = 0.200), history of pumonary disease (sig = 1), smoking habits (sig = 0.670), exercise habits (sig = 0.062), and exposure to PM2.5 dust (sig = 0.797) had no association with pulmonary function disorders in Semarang BRT drivers. Researchers suggest the company install dust filters on buses and filter cleanings twice a month and inform them about PM2.5 dust as well as calls to prevent preventive health.